Liposuction-Augmentation Mammaplasty. (16th October 2017) - Harris, Ryan; Raphael, Peter; Harris, Scott W
Abstract: Background: The female breast loses superior fullness and becomes more ptotic over time. Women often present to their plastic surgeon requesting reversal of this evolution. While liposuction alone has been proven to lift the breast, no solution combining augmentation and liposuction has been reported. Objectives: Herein, we introduce a technique called liposuction-augmentation mammaplasty (LAM) that can achieve "scarless" lifting or simply volume equalization prior to inserting same-sized implants. We then compare its safety and efficacy to two gold-standard techniques with similar aims, mastopexy-augmentation mammaplasty (MAM) and reduction-augmentation mammaplasty (RAM). Methods: A retrospective 3-year chart review was conducted on 359 patients (652 breasts) undergoing LAM (n = 125), MAM (n = 188), and RAM (n = 46). Patient demographics, operative details, and revisions were documented. Degree of lift was measured on pre- and postoperative photographs using sternal notch-to-nipple distances (SN-N). Statistical differences were assessed between the groups. Results: The LAM group's mean age and OR time (37 years, 46 minutes) were significantly lower than those of MAM (43 years, 90 minutes) and RAM (42 years, 106 minutes). Mean BMIs and revision rates were uniform between the LAM and MAM groups (24, 2.5%), but significantly higher for RAM (28, 4.6%). Aspirate volumes and resection weights averaged 151 cc and 307 g (left breast) and 173 cc and 298 g (right breast). Minimum follow up was 12 months. The LAM group's mean SN-N reduction (~6%) was statistically significant, albeit much lower than MAM (~16%) and RAM (~22%). Conclusions: LAM is a safe, facile, reliable solution for the ptotic, fatty breast. Patients can direct their volumetric outcome and enjoy lower costs and shorter downtime. Level of Evidence: 3: